Effect of Inoculation On Microstructure, Mechanical and Corrosion Properties of High Manganese Ductile Ni-resist Alloy - Mohd Rashidi, Maarof; Mohd Hasbullah, Idris (Elsevier, 2013)
The performance of modified Ductile Ni-Resist (DNR) adapted with higher manganese content, may be improved by inoculation in order that it may be of use in corrosive and high temperature application. In this study, DNR cast alloy was casting to different manganese content before undergoing inoculation process with various inoculation percentages. Scanning Electron Microscope / Energy Dispersive X-ray Spectroscopy SEM/EDS characterized the corrosion products. The results showed that increasing inoculation did decreased carbide formation led to improved tensile value and decreased hardness value. Moreover, inoculation led to uniform distribution of graphite resulted in lower corrosion rates. It can be concluded that inoculation process improved the mechanical properties of the alloy and satisfy the corrosion resistance criteria required for corrosive environment.